Identifikasi Tingkat Kecemasan Pre Operasi Pasien Fraktur di Ruang Aster dan Cempaka RSUD Abdul Wahab Sjahranie Samarinda - Diah Setiani (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: In Indonesia, High mobility and human careless become one of the factors of traffic accident. The total number of traffic accident that occured, there were 5.8 % injures or about eight million people was suffering form fractures with the most common fracture type that often occurs, that was 36.9% limb fractures in the upper extremity and 65,2% limb fracture in lower extremity (Departemen Kesehatan Republik Indonesia, 2013). When people had limb fracture,surgery become one of efforts to restore the structure and the function of the bones into the initial condition. According to the medical data record of Abdul Wahab Sjahranie Hospital Samarinda in 2016, The number of patient who had ortopedic surgery was about 1.579 people. Smeltzer and Bare (2002) stated that Surgery is something that can cause the anxiety. Accordng to Carpenito (2002) 90% pra-surgery patient potentially had anxiety. In determining the level of that anxiety, it is necessary to have valid dan realiable asessment instrument that has been tested by using Hamillton Anxiety Rating Scale (HARS). Purpose of study: To know descreption level anxienty patient of pra surgery on fracture patient. Method : research description to approach methode cross sectional study. Technique taking sample to this reasearch is using accidental sampling methode obtained respondent as much 17 person in mei until july 2017 at aster room and cempaka room of RSUD Abdul Wahab Sjahranie Samarinda. Result : based on univariat analysis, fraction have 2 (11,8%) not anxiety and 5 (29,4%) have mild anxiety, while most of the 10 (58,8%) respondent have moderate anxiety.Conclusion : level anxiety on patient pre surgery who have fractur, most of the 10 (58,8%) respondet have moderate anxiety.